2021
DOI: 10.1007/s10409-020-01026-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrical stimulation on skin surface

Abstract: Skin is the largest organ in the body, and directly contact with the external environment. Articles on the role of micro-current and skin have emerged in recent years. The function of micro-current is various, including introducing various drugs into the skin locally or throughout the body, stimulating skin wounds healing through various currents, suppressing pain caused by various diseases, and promoting blood circulation for postoperative muscle rehabilitation, etc. This article reviews these efforts. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 114 publications
0
18
0
Order By: Relevance
“…In a trial examining the safety and efficacy of MCT for sinus pain and congestion, it was concluded that MCT is safe with only minor side effects (tingling in the feet), which were resolved without medical intervention (Goldsobel et al 2019). MCT has been applied in many medical scenarios, being reported as a safe therapy over the decades (Al-Tubaikh 2018;Xu et al 2021). Indeed, in the two interventional studies conducted by our research group, no side effects associated with the use of MCT were reported (Naclerio et al 2021(Naclerio et al , 2019.…”
Section: Side Effects Of Using Microcurrent In Healthy Humansmentioning
confidence: 99%
“…In a trial examining the safety and efficacy of MCT for sinus pain and congestion, it was concluded that MCT is safe with only minor side effects (tingling in the feet), which were resolved without medical intervention (Goldsobel et al 2019). MCT has been applied in many medical scenarios, being reported as a safe therapy over the decades (Al-Tubaikh 2018;Xu et al 2021). Indeed, in the two interventional studies conducted by our research group, no side effects associated with the use of MCT were reported (Naclerio et al 2021(Naclerio et al , 2019.…”
Section: Side Effects Of Using Microcurrent In Healthy Humansmentioning
confidence: 99%
“…In recent years, many therapies aiming at stimulating the healing process are in clinical use, such as ultrasound, laser therapy, and other forms of photobiomodulation, electrical stimulation, hyperbaric oxygen, and vacuum-assisted closure (Dreifke et al, 2015;Nesi-Reis et al, 2018;Priyadarshini et al, 2018;Micheli et al, 2019;Xu et al, 2021). The efficacy of physical approaches is due to the fact that all the cell types involved in wound healing (fibroblasts, keratinocytes, and ECs) are sensitive to mechanical forces at cellular and molecular level acting as mechanotransducers.…”
Section: Physical Countermeasuresmentioning
confidence: 99%
“…The skin is considered the largest human organ that protects the outer body against the external environment. This includes physical, chemical, and microbial invasion, which lead to skin injury or trauma upon exposure [ 1 , 2 , 3 ]. Skin wounds and complicated wound-healing processes affect about one billion people worldwide and have an enormous influence on the human health care system, leading to an increase in financial cost [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%